Red propolis and L-lysine on angiogenesis and tumor growth in a new model of hamster cheek pouch inoculated with Walker 256 tumor cells - Juanes, Camila de Carvalho (Einstein (Sao Paulo), 2019)
OBJECTIVE: To evaluate the effect of red propolis and L-lysine on angiogenesis and tumor growth in a new model of hamster cheek pouch inoculated with Walker 256 tumor cells. METHODS: The study consisted of two experiments with four groups each (total: 57 hamsters). In the experiment 1, the animals were inoculated with Walker tumor cells, followed by administration of test substances (red propolis 200mg/5mL/kg or L-lysine 150mg/kg) or control substances (gum arabic 5mL/kg or water 5mL/kg) for 10 days. The animals in the experiment 2 received red propolis, L-lysine, gum arabic or water at the same doses, for 33 days prior to inoculation of Walker tumor cells, followed by 10 days of treatment with the same substances. Based on single-plane images, angiogenesis was quantified (mean vascular area), in percentage, and tumor area (mm(2)) and perimeter (mm). RESULTS: In the experiment 1, compared to animals receiving water, the mean vascular area expressed in percentage was significantly smaller in animal treated with propolis (p<0.05) and L-lysine (p<0.001). CONCLUSION: Both red propolis and L-lysine inhibited tumor angiogenesis in the new hamster cheek pouch model when administered after tumor inoculation.